A middle-aged man with a troubled liver: Combination therapy in advanced (BCLC Stage C) hepatocellular carcinoma - Zamri Zuhdi; Azlanuddin Azman; Affirul Chairil Ariffin; Razman Jarmin; Hairol Azrin Othman (Sageya Publisher, 2024)
Non-Indexed Publication